2018
DOI: 10.1080/21505594.2018.1532243
|View full text |Cite
|
Sign up to set email alerts
|

BabA-mediated adherence of pediatric ulcerogenic H. pylori strains to gastric mucins at neutral and acidic pH

Abstract: 2018)BabA-mediated adherence of pediatric ulcerogenic H.pylori strains to gastric mucins at neutral and acidic pH, ABSTRACT Helicobacter pylori infection can result in non-ulcer dyspepsia (NUD), peptic ulcer disease (PUD), adenocarcinoma, and gastric lymphoma. H. pylori reside within the gastric mucus layer, mainly composed of mucins carrying an array of glycan structures that can serve as bacterial adhesion epitopes. The aim of the present study was to characterize the binding ability, adhesion modes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…We have previously demonstrated that H. suis binding occurs via two modes of adhesion: (1) to galactose-terminating structures at both neutral and acidic pH and (2) to negatively charged structures at acidic pH. 18 In contrast to the large variation in mucin-binding specificity and avidity present among H. pylori strains, 38 binding of four H. suis strains isolated from primates and pigs to pig and human mucins was very similar, 18 suggesting low inter-individual variation in binding specificity among H. suis strains. Here, we showed that the binding level of H. suis to pig gastric mucins was around sevenfold higher at pH 2 than at pH 7, regardless of the infection status of the pigs.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that H. suis binding occurs via two modes of adhesion: (1) to galactose-terminating structures at both neutral and acidic pH and (2) to negatively charged structures at acidic pH. 18 In contrast to the large variation in mucin-binding specificity and avidity present among H. pylori strains, 38 binding of four H. suis strains isolated from primates and pigs to pig and human mucins was very similar, 18 suggesting low inter-individual variation in binding specificity among H. suis strains. Here, we showed that the binding level of H. suis to pig gastric mucins was around sevenfold higher at pH 2 than at pH 7, regardless of the infection status of the pigs.…”
Section: Discussionmentioning
confidence: 99%
“…hyodysenteriae growth in the presence of mucins and monosaccharides. Bacterial growth in the presence of mucins was performed as previously described (52). Mucins were dialyzed against four changes of 2 M NaCl, followed by two changes against sterile PBS.…”
Section: Methodsmentioning
confidence: 99%
“…In Western countries, infection with BabA producing strains has been associated with an increased risk for peptic ulcer disease development [91,92]. A recent study highlighted the adherence of strains with a high avidity mediated by BabA-positive pediatric ulcerogenic H. pylori strains [93].…”
Section: Virulence Factors Associated With Colonization Of Epithelmentioning
confidence: 99%